2023
DOI: 10.1097/01.numa.0000905032.53383.4e
|View full text |Cite
|
Sign up to set email alerts
|

Renewing the care team model

Abstract: Due to staffing challenges, a large healthcare system revisited the care team model, incorporating the LPN role. LPNs were effectively integrated into medical-surgical and ED settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Staffing shortages have required hospitals to reevaluate traditional RN models of care delivery, as well as the staffing level and skill mix of clinicians 1. For example, licensed practical nurses (LPNs) were introduced into acute care areas to support RNs8; however, one study found that even within total care delivery models, LPNs were a regular part of the staffing mix 9. Changing the skill mix of nurses in acute care can not only lead to challenges with collaborative relationships,10 role confusion,11 and adverse patient outcomes12 but can also result in positive outcomes such as lower levels of nurse exhaustion,9 turnover,13 infection rates,14 and promotion of better teamwork and communication among nurses 15…”
mentioning
confidence: 99%
“…Staffing shortages have required hospitals to reevaluate traditional RN models of care delivery, as well as the staffing level and skill mix of clinicians 1. For example, licensed practical nurses (LPNs) were introduced into acute care areas to support RNs8; however, one study found that even within total care delivery models, LPNs were a regular part of the staffing mix 9. Changing the skill mix of nurses in acute care can not only lead to challenges with collaborative relationships,10 role confusion,11 and adverse patient outcomes12 but can also result in positive outcomes such as lower levels of nurse exhaustion,9 turnover,13 infection rates,14 and promotion of better teamwork and communication among nurses 15…”
mentioning
confidence: 99%